MENINGKATKAN KEDISIPLINAN MELALUI GOOGLE CLASSROOM DALAM MATA KULIAH BAHASA INDONESIA - Lilis Amaliah Rosdiana; Sary Sukawati; Dida Firmansyah (Jurnal Semantik, 2020)
This study tries to apply online learning based on information technology that allows students to have freedom in learning without being limited by space and time in learning. The discussion in this study is limited to the effectiveness of using google classroom as a medium of learning and task collection, so the objective to be obtained in this research is to find out the increase in student discipline in collecting Indonesian course assignments using Google Classroom. The problem that occurs is the collection of tasks carried out manually (collecting assignments in the form of paper printouts), students often ask for additional time to collect these assignments. With this google classroom, students cannot lobby anymore because there is a time limit that cannot be changed. This research method uses a descriptive qualitative method. The collection of assignments three times in one semester. The results obtained are when gathering the 1st assignment, out of a total of 36 students, only 21 succeeded in collecting the assignments on time. The second assignment had more people who collected assignments on time, namely 30 students from a total of 36 students. In the third assignment, all students collect assignments promptly. So, this google classroom has been proven to increase discipline in gathering assignments, especially in Indonesian Language courses.